Superplastic Forming/Diffusion Bonding of TA15 Titanium Alloy for Manufacturing Integrated Solid/Hollow Four-Layer Grid Lightweight Structure Components - Zheng Han; Yuhan Xing; Taiying Liu; Ning Zhang; Shaosong Jiang; Zhen Lu (Metals)
In recent years, the excellent mechanical properties and lightweight characteristics of multi-layer hollow components have led to a surge in research focused on their forming processes. This growing interest has greatly advanced technological progress in aerospace and other related fields. In this paper, the metal flow behavior of TA15 titanium alloy at different temperatures from 840 °C to 940 °C and different strain rates from 0.001 s−1 to 0.1 s−1 was studied. Utilizing the finite element method, this study examined the local stress concentration, total strain distribution, thickness thinning characteristics, and pressure loading control during the superplastic forming process of the component. The integrated solid/hollow four-layer grid lightweight structural parts were successfully fabricated using the superplastic forming/diffusion bonding (SPF/DB) process. The quality of the components was evaluated using X-ray and ultrasonic C-scan detection methods. The results show that the maximum elongation of the alloy is 1340% at 900 °C/0.001 s−1. When the temperature is too high, the grain size increases remarkably, and the elongation decreases. Based on the finite element simulation results, 900 °C is the best superplastic forming temperature. Under this temperature parameter, the maximum thinning rate of the core sheet is 39.7%, the SPF time is 10,000 s, the maximum thinning rate of the face sheet is 9.8%, and the SPF time is 2400 s. In addition, the solid block has a minimal effect on the thinning of the core sheet. The grid exhibits obvious stress concentration and thinning at its rounded corners, while the thickness distribution in other areas remains relatively uniform. The nondestructive testing results confirmed that the ribs of the component are fully formed, with no missing or broken ribs. The grid exhibits good geometry and high-quality diffusion bonding. The average thickness at key positions of the component is 1.84 mm, with the minimum thickness being 1.7 mm. As the size of the grid cavity decreases, the thickness of the component tends to increase gradually. The maximum error between the simulated and measured values is 4.47%, indicating good accuracy in the simulation. Additionally, the thickness distribution of the component is relatively uniform.